Disseminating sexually transmitted infections diagnostics information: the SDI web publication review series. (20th November 2006) - Kuypers, J; Tam, M R; Holmes, K K; Peeling, R W
Abstract : Objectives: The World Health Organization Sexually Transmitted Diseases Diagnostics Initiative (SDI) website publication review seeks to provide health care providers in all geographic and economic settings with timely, critical, and concise information concerning new developments in laboratory and field diagnosis of sexually transmitted infections (STI). Methods: Since 2003, the website (www.who.int/std_diagnostics/literature_reviews ) has disseminated information in the form of annotated abstracts and commentaries on articles covering studies of STI laboratory-based and rapid assays that are commercially available or under development. Articles identified through searches of PubMed, specific journals, and by referrals from Editorial Board members are selected for inclusion if they meet pre-specified criteria. The objectives, methods, results, and conclusions for each article are summarised and board members are invited to prepare commentaries addressing study design and applicability of findings to end users. Results: Currently, 91 STI diagnostics experts from 17 countries on six continents serve on the Editorial Board. Twelve quarterly issues have been posted that include summaries of 214 original and 17 review articles published from January 2002 through March 2005, with expert commentaries on 153 articles. Interest in the site has increased every year. In 2005, over 36 700 unique visitors from more than 100 countries viewed over 75 000 pages of information. Conclusions: The SDI Publication Review series has the potential to contribute to SDI's goal of improving care for patients with STI by increasing knowledge and awareness of STI diagnostics. Given the proliferation of internet-based STI testing services, this website may be broadened to meet the needs of a wider range of users.